EPR spectroscopy of 5-DOXYL-stearic acid bound to the mitochondrial uncoupling protein reveals its competitive displacement by alkylsulfonates in the channel and allosteric displacement by ATP - Jezek, P; Bauer, M; Trommer, W E (FEBS letters, 1995)
Competition of fatty acids (FA) and alkylsulfonates with 5-DOXYL-stearic acid (5-SASL) binding to isolated mitochondrial uncoupling protein (UcP) is demonstrated using EPR spectroscopy. A distinct peak of the bound 5-SASL (h+1I) decreased with increasing concentration of competitors. Since alkylsulfonates are UcP substrates, it suggests that the FA binding site is located in the anion channel. Moreover, with increasing ATP the h+1I peak decreased and was smoothed with the 'micellar' peak into a single wider peak. A pH of 8.5 reversed this effect. It could reflect an allosteric release of 5-SASL from the ATP binding site which mimics the ATP gating mechanism.
Keywords: kyseliny mastné neesterifikované; Carrier Proteins; Ion Channels; elektronová paramagnetická rezonance; Allosteric Regulation; křeček rodu Mesocricetus; transportní proteiny; kyseliny sulfonové; Spin Labels; Fatty Acids, Nonesterified; Cricetinae; Electron Spin Resonance Spectroscopy; alosterická regulace; Kinetics; Mesocricetus; Uncoupling Protein 1; Cyclic N-Oxides; kinetika; mitochondrie; uncoupling protein 1; Adipose Tissue, Brown; mitochondriální proteiny; Mitochondria; křečci praví; membránové proteiny; zvířata; iontové kanály; Membrane Proteins; Animals; Binding, Competitive; Sulfonic Acids; spinové značení; hnědá tuková tkáň; cyklické N-oxidy; kompetitivní vazba; Mitochondrial Proteins